Nietzsche la verdad es mujer - Munnich, Susana.. (Santiago de Chile, Chile : LOM Ediciones, 2011)
"It has long been said that Nietzsche was not exactly a philosopher but a poet. However, when we examine his texts, researchers forget to offer systematic explanations to form another analysis. This essay, published in the first edition in 1994, is faithful to the spirit of Nietzsche, who loved contradiction, play and laughter. In this way reinforces the idea of polyphony that Nietzsche formulated with the sentence: The truth is women" (fom publisher).
Prólogo -- Algunas consideraciones sobre la lectura y la escritura -- Paréntesis -- De embarazos e ideales ascéticos -- De convicciones y de mujeres -- ¿Una ontología ginecológica? -- “¡Sí, la vida es mujer!” -- Conclusión - Bibliografía.
Previously published: Editorial Universitaria, 1994.
Includes bibliographical references (p. 153-155).
Keywords: Nietzsche, Friedrich Wilhelm, -- 1844-1900 -- Views on women; Women; Electronic books